Transformation of Mosque Management Through Islamic Social Enterprise Concept - Rizqi Anfanni Fahmi (Department of Islamic Economics, Islamic University of Indonesia, 2022)
Mosque management tends to be traditional and still relies on donations from congregations to finance mosque activities. So far, studies related to the transformation of mosque management tend to discuss information system management and mosque finances. This paper aims to complete the shortcomings of the existing studies by offering the transformation of mosque management through the concept of Islamic Social Enterprise. This study uses a literature study approach from various journal articles, books, and online news related to mosque management, Islamic Social Enterprise, and mosque business units. This study is a conceptual text to formulate the transformation of mosque management toward the concept of Islamic Social Enterprise. The findings of this study indicate three main points. First, there is an urgency to transform the mosque. Second, the relevance of Islamic Social Enterprise characteristics with mosques in the form of mosque business units. Third, from the examples of several mosques, it is found that there are indications that the mosque business unit has a contribution to the mosque's income and the economic welfare of the community. This paper contributes to strengthening efforts to improve the performance and usefulness of mosques as non-profit organizations.